2009
DOI: 10.1088/0957-4484/20/29/295501
|View full text |Cite
|
Sign up to set email alerts
|

SERS detection of low-concentration adenine by a patterned silver structure immersion plated on a silicon nanoporous pillar array

Abstract: A patterned Ag structure was grown on a Si nanoporous pillar array (Si-NPA) by an immersion plating method, and its surface-enhanced Raman scattering (SERS) activity toward adenine was studied. It was shown that two kinds of Ag structures were grown on Si-NPA, a continuous film covering the Si-NPA substrate and composed of Ag nanocrystallites (nc-Ag), and a quasi-regular, interconnected network composed of loop-chains of sub-micron Ag crystallites surrounding the porous Si pillars. The SERS detection of low-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 44 publications
3
56
0
1
Order By: Relevance
“…10 cm À1 ) of the ring-breathing mode when adenine is adsorbed on Ag colloids, electrodes, island films, and nanoparticles. [9,[19][20][21][22] Our measurement show a large redshift (7 cm À1 ) of the ring-breathing mode between the NRS and SERS of adenine (see Figure S4 of the Supporting Information). The frequency shifts of the ring-breathing mode in the predicted spectra of all complexes are listed in Table 1.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…10 cm À1 ) of the ring-breathing mode when adenine is adsorbed on Ag colloids, electrodes, island films, and nanoparticles. [9,[19][20][21][22] Our measurement show a large redshift (7 cm À1 ) of the ring-breathing mode between the NRS and SERS of adenine (see Figure S4 of the Supporting Information). The frequency shifts of the ring-breathing mode in the predicted spectra of all complexes are listed in Table 1.…”
mentioning
confidence: 63%
“…A simulation of adenine bound to a silver atom provided only semiquantitative agreement with the SERS spectra. [19] A more notable study of adenine bound to a large Ag 20 cluster via N7 predicted a Raman spectrum with small intensity for the ringbreathing mode, inconsistent with the typical experimental SERS spectra. [23] Thus, it is important to establish large model systems to reproduce experimental SERS spectra and understand the adsorption process of adenine on the silver surfaces.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ag colloid is mixed with the target molecule, adenine. Adenine has been used in much research on SERS, because SERS-based analysis is expected to have potential in label-free sequencing of DNA/RNA (Feng et al 2009;Papadopoulou and Bell 2010). The mixed solution is added to a sample plate with a small chamber fabricated by an acrylic plate, a cover glass, and silicon rubber spacers.…”
Section: Sers Detection Of Biomolecules With Optical Trapping Of Ag Nmentioning
confidence: 99%
“…It has been proved that the porous Si (PS) can increase the amount of the effective hot spots and further enhance the sensitivity of the SERS signals with the assist of the large specific area and nanoporous governable structure1213141516. Recently, some groups have reported different SERS substrates based the PS, such as PS decorated with Au nanoparticles1217 and Ag-coated Si nanoporous1819. Very recently we found that the local electric field enhancement on the CuNPs/Cu foil is stronger than that on CuNPs/SiO 2 substrate.…”
mentioning
confidence: 99%